2017
DOI: 10.1155/2017/3543681
|View full text |Cite
|
Sign up to set email alerts
|

Low Prevalence of Clinically Significant Endoscopic Findings in Outpatients with Dyspepsia

Abstract: Background. The value of endoscopy in dyspeptic patients is questionable. Aims. To examine the prevalence of significant endoscopic findings (SEFs) and the utility of alarm features and age in predicting SEFs in outpatients with dyspepsia. Methods. A retrospective analysis of outpatient adults who had endoscopy for dyspepsia. Demographic variables, alarm features, and endoscopic findings were recorded. We defined SEFs as peptic ulcer disease, erosive esophagitis, malignancy, stricture, or findings requiring sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
30
3
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 42 publications
14
30
3
3
Order By: Relevance
“…We observed that epigastric pain was the most common presenting symptom (79.2%) in the overall study population, which is consistent with the ndings of previous study by Khaled et al who reported it as 76.6% [20], while it was reported as 34% in another study [24]. Our study revealed a higher prevalence of gastritis than other diseases (65.5%) which is higher than the past reported rates [20,22,24].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…We observed that epigastric pain was the most common presenting symptom (79.2%) in the overall study population, which is consistent with the ndings of previous study by Khaled et al who reported it as 76.6% [20], while it was reported as 34% in another study [24]. Our study revealed a higher prevalence of gastritis than other diseases (65.5%) which is higher than the past reported rates [20,22,24].…”
Section: Discussionsupporting
confidence: 91%
“…Thomson et al where they found malignancy only in 2 patients and both were above 50 years of age [24]. Similarly other studies also reported a low prevalence of malignancy 0.8% [20]. In our study the prevalence rates of gastric and duodenal ulcer were found to be 4.6 and 5.9 respectively.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Esto fue confirmado también en nuestra serie: la úlcera gástrica (3,7%) fue más frecuente que la úlcera duodenal (2,7%), y sólo 51% de las úlceras gástricas y 46% de las úlceras duodenales fueron positivas para infección por HP, lo que puede deberse al mayor uso de antiinflamatorios no esteroidales. La baja frecuencia de úlcera péptica en nuestro centro es concordante con nuestra baja prevalencia de infección por HP (28,9%), lo que coincide con lo encontrado en otras series 26 . En contraste, en La Florida, Chile, con una prevalencia de infección por HP de 78%, se encontró mayor prevalencia de úlcera péptica, con 8,1% de pacientes con úlcera gástrica y 6,4% de pacientes con úlcera duodenal 3 .…”
Section: Discussionunclassified